NON-TRADITIONAL SECURITY THREAT: IMPACT AND CHALLENGE ON MALAYSIAN SECURITY - Zahimi Zainol Abidin; Mohd Faizal Mohd Jais (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This study aims to analyse the impact of non-traditional security threats on Malaysia’s security, identify the critical challenges posed by these threats, and propose recommendations for enhancing Malaysia’s capacity to address them effectively. The investigation into Malaysia’s non-traditional security concerns was conducted through a rigorous and comprehensive analysis process involving information gathered from various sources. This approach allows researchers to gain a deeper understanding of such threats and their prevalence in the country. The study also examines their effects on national security policy, providing valuable insights that can aid in formulating countermeasures to safeguard Malaysia’s interests and bolster its resilience. In this research paper, a qualitative approach is employed, utilizing secondary data from articles, reports, and relevant documents related to non-traditional security threats. The research objectives are to analyse the impact of these threats on Malaysia’s security, identify the key challenges posed, and propose recommendations for enhancing the capacity of both government and private entities to address these issues.